Myths and places: new perspectives in Indian cultural geography - Kaul, Shonaleeka (Routledge, Taylor & Francis Group, 2023)
This volume explores the dialogic relationship between myths and places in the historically, geographically and culturally diverse context of India
Keywords: Asia; India; Indien; Mythologie; Heiligtum; Historische Geografie